Social Contracts and Informal Workers in the Global South - Alfers, Laura; Chen, Martha; Plagerson, Sophie (Edward Elgar Publishing, 2022)
This is an open access title available under the terms of a CC BY-NC-ND 4.0 License. It is free to read, download and share on Elgaronline. Illustrating how current social contracts may be considered inadequate, irrelevant or unjust, Social Contracts and Informal Workers in the Global South draws on the accounts of informal workers to advocate for radically new conceptualizations of state-society, capital-labour and state-capital-labour relations characterised by recognition, responsiveness and reciprocity.